Effect of tagitinin C isolated from Tithonia diversifoli (Hemsley) A Gray on migration activity and TGF-β1 levels on keloid fibroblast - Elvira Santi; Mae Sri Hartati Wahyuningsih; Arief Budiyanto (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2019)
Keloid is the formation of excessive scar tissue characterized by fibroblast hiperproliferations and collagen deposits that are similar with cancer cells. Tagitinin C is proven can inhibit proliferation and deposition of keloids collagen fibroblast. However, the mechanism of action of tagitinin C in migration activities and TGF-β1 levels of keloid fibroblasts has not been proved, yet. This study aimed to investigate the effects of tagitinin C isolated from Tithonia diversifoli (Hemsley) on migration activity and TGF-β1 expression of keloid fibroblast. This was quasi experimental study with post test only controlled group design using keloid fibroblasts isolated from keloid patients. The migration activity were performed by scratch assay and TGF-β1 levels were measured using an ELISA kits. Isolate tagitinin C was more active inhibit fibroblast keloid migration compare to the control groups (p<0.05) after 48 h incubation. TGF-β1 levels after incubation with isolate tagitinin C was lower then control group (p<0.05). In conclusion, isolate tagitinin C can inhibit migration and reduce TGF-β1 levels on keloid fibroblast